People’s Participation in Implementation of Soil and Water Conservation Programme: Case Study of Antisar Watershed in Kheda District of Gujarat (Indian Journal of Extension Education, 2018)
The study was conducted in the Integrated Wasteland Development Project (IWDP), Antisar watershed located in Kapadwanj Taluka of Kheda district in Gujarat. It was revealed that majority more than three fourth of the respondents (76.02%) showed moderate level of participation, nearly one fifth of them (19.64%) having low participation level and few of them with high participation level in implementation of the soil and water conservation technologies in the watershed development programme. The overall extent of the male as well as female beneficiary farmers’ participation in the programme at the stage of its implementation was calculated with the help of People’s Participation Index (PPI) and it was found 69.29 per cent and 71.66 per cent respectively. It means that overall extent of participation of male and female farmers in the implementation stage was high level. The variables socio-economic status, farm power, risk preference, knowledge and attitude were positively and significantly correlated with the participation of male farmers in implementation of SWC programme. Whereas, the variables socio-economic status, education, family size, social participation, risk preference, knowledge and attitude were positively and significantly correlated with the participation of female farmers in implementation of SWC programme, and the variables age and income were negatively and significantly correlated with the participation of female farmers in implementation of soil and water conservation programme.